1987
DOI: 10.1007/bf00583796
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic, α1 and peptidergic agonists stimulate phosphoinositide hydrolysis and regulate mucin secretion in rat submandibular gland cells

Abstract: Three classes of agonists associated with Ca2+-mobilization--alpha 1-adrenergic (methoxamine), muscarinic (carbachol) and peptidergic (substance P, SP)--significantly stimulated the secretion of mucin from enzymatically-dispersed rat submandibular gland acinar cells. The same three secretagogues also caused the hydrolysis of membrane inositol phospholipids, resulting in elevated cellular levels of inositol phosphates, particularly inositol 1,4,5-trisphosphate (IP3). Exogenous IP3 elicited the dose-dependent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Signal transduction mechanism underlying stimulation of muscarinic cholinergic receptors in salivary glands involves G‐proteins activation resulting in hydrolysis of phosphatidylinositol biphosphate by phospholipase C and thereby production of phosphatidylinositol 1,4,5‐triphosphate (IP 3 ) which leads to a rise in the intracellular calcium concentration and consequently to fluid secretion (Fleming et al , 1987; Nauntofte, 1992). It has been demonstrated that lithium interferes with phosphatidylinositol turnover in rat brain slices and parotid fragments, by inhibiting inositolmonophosphatase and consequently decreasing level of IP 3 in uncompetitive and time‐dependent manner (Berridge et al , 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal transduction mechanism underlying stimulation of muscarinic cholinergic receptors in salivary glands involves G‐proteins activation resulting in hydrolysis of phosphatidylinositol biphosphate by phospholipase C and thereby production of phosphatidylinositol 1,4,5‐triphosphate (IP 3 ) which leads to a rise in the intracellular calcium concentration and consequently to fluid secretion (Fleming et al , 1987; Nauntofte, 1992). It has been demonstrated that lithium interferes with phosphatidylinositol turnover in rat brain slices and parotid fragments, by inhibiting inositolmonophosphatase and consequently decreasing level of IP 3 in uncompetitive and time‐dependent manner (Berridge et al , 1982).…”
Section: Discussionmentioning
confidence: 99%
“…We have also found that chronic administration of lithium reduces phenylephrine‐induced secretory response in uncompetitive manner, as in the case of carbachol. Phenylephrine, as a selective α 1 agonist, produces salivation because of activation of α 1 adrenoceptor associated with phosphoinositide signalling (Fleming et al , 1987). The inhibitory effect of lithium on phenylephrine‐induced secretion supports the suggestion that its antisialogouge effect could be a consequence of its interference with phosphatidylinositol turnover.…”
Section: Discussionmentioning
confidence: 99%
“…The salivary glands of the head derive their innervation from both the adrenergic and cholinergic branches of the autonomic nervous system [8], with cholinergic stimulation being more important for the secretion of water and electrolytes [11,17,21] but less important for that of protein (e.g., amylase) and mucous substances [3,7]. During cholinergic stimulation of a salivary gland there occurs a rise in intracellular Ca 2+ concentration [15].…”
Section: Discussionmentioning
confidence: 99%